2008 Annual Computer Security Applications Conference (ACSAC) 2008
DOI: 10.1109/acsac.2008.45
|View full text |Cite
|
Sign up to set email alerts
|

Defending Against Attacks on Main Memory Persistence

Abstract: Main memory contains transient information for all resident applications. However, if memory chip contents survives power-off, e.g., via freezing DRAM chips, sensitive data such as passwords and keys can be extracted. Main memory persistence will soon be the norm as recent advancements in MRAM and FeRAM position non-volatile memory technologies for widespread deployment in laptop, desktop, and embedded system main memory. Unfortunately, the same properties that provide energy efficiency, tolerance against powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Researchers have had quite a bit of success in retrieving encryption keys from active system memory. In order for this attack vector to be successful the adversary must have physical privileged access to the machine on which the software is running as was the case in the research presented here [7]. Several recent research projects have reported great success in retrieving plaintext passwords using the same attack vector [8].…”
Section: Figure 1 Typical Database Connection Scenariomentioning
confidence: 91%
“…Researchers have had quite a bit of success in retrieving encryption keys from active system memory. In order for this attack vector to be successful the adversary must have physical privileged access to the machine on which the software is running as was the case in the research presented here [7]. Several recent research projects have reported great success in retrieving plaintext passwords using the same attack vector [8].…”
Section: Figure 1 Typical Database Connection Scenariomentioning
confidence: 91%
“…The concept of attacking persistence in main memory [33] is to read memory containing passwords or other secret data that is not consciously erased between users.…”
Section: Softwarementioning
confidence: 99%
“…A particularly extreme example is attacking main memory persistence. A solution to this problem has been addressed for the traditional and Internet cases [33]. Specifically research on cryptographic methods for authenticating data stored in servers [15].…”
Section: Secure Storage and Computationmentioning
confidence: 99%
“…Due to a large separation between the lowest and the highest resistance state, both PCM and RRAM NVMs support multi-level/triple-level cell (MLC/TLC) operation, which is the ability to store 2/3 logical bits per physical cell. Whereas PCM/RRAM NVMs have emerged as promising DRAM replacements, data persistence in PCM/RRAM NVMs poses many security vulnerabilities that must be addressed prior to commercialization of these advanced NVM technologies [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%